2015
DOI: 10.1515/jppr-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

ITS sequence data and morphology differentiate Cytospora chrysosperma associated with trunk disease of grapevine in northern Iran

Abstract: Trunk diseases are potential threats for the grapevine industry owing to the worldwide incidence and economic impact of the diseases. Several fungal groups are known to be involved in these diseases. In a survey on grapevine trunk diseases in northern Iran, Cytospora isolates were repeatedly recovered from vines showing decline symptoms. The symptoms appeared as pale brown to brown streaks in longitudinal cuts of shoots. The morphological and cultural characteristics of the isolates were in agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Previous studies show most trunk pathogens require up to a year to cause significant lesions within living grapevines (Lawrence et al ., ; Travadon et al ., ). Indeed, the 12 cm lesions measured by Arzanlou & Narmani () after 28 days in detached canes are much larger compared to 2 cm lesions in live woody stems after 12 months in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Previous studies show most trunk pathogens require up to a year to cause significant lesions within living grapevines (Lawrence et al ., ; Travadon et al ., ). Indeed, the 12 cm lesions measured by Arzanlou & Narmani () after 28 days in detached canes are much larger compared to 2 cm lesions in live woody stems after 12 months in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Recently, C . chrysosperma , the type species for the genus, was also reported in Iran from grapevines displaying decline symptoms, including stunted growth, canopy chlorosis and necrosis, and black vascular streaking or discoloured wood (Arzanlou & Narmani, ). Pathogenicity assays conducted on excised, 1‐year‐old grapevine shoots revealed that two of four isolates of C .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Clade stability was assessed using 1000 bootstrap replications (Felsenstein 1985). Diaporthe eres was used as the outgroup in the phylogenetic analyses (Arzanlou and Narmani 2015). The Neighbour-Joining (NJ) analysis showed that isolate CYH1 (IRAN 2642C), obtained from the cankered peach twigs, clustered with authentic isolates of C. chrysosperma (Fig.…”
mentioning
confidence: 99%
“…4). Pathogenicity tests were performed on excised shoots in laboratory conditions as described by Arzanlou and Narmani (2015). In total, 15 healthy shoots a year-old were cut from trees.…”
mentioning
confidence: 99%